Effect of resistance exercise contraction mode and protein supplementation on members of the STARS signalling pathway. (3rd July 2013) - Vissing, Kristian; Rahbek, Stine K.; Lamon, Severine; Farup, Jean; Stefanetti, Renae J.; Wallace, Marita A.; Vendelbo, Mikkel H.; Russell, Aaron
Key points: Myocellular protein signalling constitutes an important regulatory process influencing skeletal muscle cell size and remodelling as an adaptation to exercise and training. Findings suggest that the striated muscle activator of Rho signalling (STARS) pathway is involved in exercise‐induced muscle hypertrophy and/or remodelling, but its regulation by different exercise modes is not well understood. In a comparative study including single‐bout exercise and training, we investigated the mRNA and protein regulation of STARS and members of its signalling pathway in response to eccentric versus concentric resistance exercise and protein supplementation. Our data show that components of the STARS signalling pathway exhibit transient regulation in response to resistance exercise, but not to resistance training, and show contraction mode‐specific regulation at the level of gene and protein expression. The results suggest that STARS signalling is important for the initiation of myocellular adaptations to resistance exercise that are dependent on contraction mode, but independent of protein supplement. Abstract The striated muscle activator of Rho signalling (STARS) pathway is suggested to provide a link between external stress responses and transcriptional regulation in muscle. However, the sensitivity of STARS signalling to different mechanical stresses has not been investigated. In a comparative study, we examined the regulation of the STARS signalling pathway in response to unilateral resistance exercise performed as either eccentric (ECC) or concentric (CONC) contractions as well as prolonged training; with and without whey protein supplementation. Skeletal muscle STARS, myocardian‐related transcription factor‐A (MRTF‐A) and serum response factor (SRF) mRNA and protein, as well as muscle cross‐sectional area and maximal voluntary contraction, were measured. A single‐bout of exercise produced increases in STARS and SRF mRNA and decreases in MRTF‐A mRNA with both ECC and CONC exercise, but with an enhanced response occurring following ECC exercise. A 31% increase in STARS protein was observed exclusively after CONC exercise ( P < 0.001), while pSRF protein levels increased similarly by 48% with both CONC and ECC exercise ( P < 0.001). Prolonged ECC and CONC training equally stimulated muscle hypertrophy and produced increases in MRTF‐A protein of 125% and 99%, respectively ( P < 0.001). No changes occurred for total SRF protein. There was no effect of whey protein supplementation. These results show that resistance exercise provides an acute stimulation of the STARS pathway that is contraction mode dependent. The responses to acute exercise were more pronounced than responses to accumulated training, suggesting that STARS signalling is primarily involved in the initial phase of exercise‐induced muscle adaptations.